Long-Term Testosterone Therapy Improves Cardiometabolic Function and Reduces Risk of Cardiovascular Disease in Men with Hypogonadism: A Real-Life Observational Registry Study Setting Comparing Treated and Untreated (Control) Groups. (September 2017) - Traish, Abdulmaged M.; Haider, Ahmad; Haider, Karim Sultan; Doros, Gheorghe; Saad, Farid
Objectives: In the absence of large, prospective, placebo-controlled studies of longer duration, substantial evidence regarding the safety and risk of testosterone (T) therapy (TTh) with regard to cardiovascular (CV) outcomes can only be gleaned from observational studies. To date, there are limited studies comparing the effects of long-term TTh in men with hypogonadism who were treated or remained untreated with T, for obvious reasons. We have established a registry to assess the long-term effectiveness and safety of T in men in a urological setting. Here, we sought to compare the effects of T on a host of parameters considered to contribute to CV risk in treated and untreated men with hypogonadism (control group). Patients and Methods: Observational, prospective, cumulative registry study in 656 men (age: 60.7 ± 7.2 years) with total T levels ≤12.1 nmol/L and symptoms of hypogonadism. In the treatment group, men (n = 360) received parenteral T undecanoate (TU) 1000 mg/12 weeks following an initial 6-week interval for up to 10 years. Men (n = 296) who had opted against TTh served as controls. Median follow-up in both groups was 7 years. Measurements were taken at least twice a year, and 8-year data were analyzed. Mean changes over time between the 2 groups were compared by means of a mixed-effects model for repeated measures, with a random effect for intercept and fixed effects for time, group, and their interaction. To account for baseline differences between the 2 groups, changes were adjusted for age, weight, waist circumference, fasting glucose, blood pressure, and lipids. Results: There were 2 deaths in the T-treated group, none was related to CV events. There were 21 deaths in the untreated (control) group, 19 of which were related to CV events. The incidence of death in 10 patient-years was 0.1145 in the control group (95% confidence interval [CI]: 0.0746-0.1756; P < .000) and 0.0092 in the T-treated group (95% CI: 0.0023-0.0368; P < .000); the estimated difference between groups was 0.0804 (95% CI: 0.0189-0.3431; P < .001). The estimated reduction in mortality for the T-group was between 66% and 92%. There were also 30 nonfatal strokes and 26 nonfatal myocardial infarctions in the control group and none in the T-treated group. Conclusion: Long-term TU was well tolerated with excellent adherence suggesting a high level of patient satisfaction. Mortality related to CV disease was significantly reduced in the T-group.